INTESTINAL MICROBIOTA AND METABOLISM: THEIR BIOCHEMICAL ROLE AS A "NEW ENDOCRINE ORGAN" IN THE HUMAN BODY (International journal of medical sciences, 2026)
The intestinal microbiota is recognized as an important regulator of metabolism in the human body. The metabolites it produces - short-chain fatty acids (SCFA), signaling molecules that activate incretin secretion, and neuroactive substances - regulate energy metabolism, insulin sensitivity, and central nervous system function. Disruption of the microbiota composition leads to a weakening of the intestinal barrier function, the development of low-grade chronic inflammation, and insulin resistance. This article analyzes the main molecular mechanisms of microbiota's influence on metabolism.